(untitled) (Journal of Economic Research & Business Administration, 2017)
The concepts of methods of forming and use of the brand communication tools has importance not only in large companies and organizations, but also in the general structures of country brand. Branding of the country - a strategic decision that requires national zeal and thorough investigation, since the state of the brand depends on the general condition of the people, its economy, financial and tourist attraction, the state and the country’s competitiveness. Therefore, in this article are provided especially for tools of integrated marketing communications for the formation of the country brand of Kazakhstan. The article includes the history and concept of country brand. Analyzing the importance of building a country brand, suggested building a national brand, which consists of the attributes of the Republic of Kazakhstan. There are missions and especially the use of integrated marketing communication. And in particular the use listed intergrirovan marketing communication for the formation of the Country Brand Republic of Kazakhstan.